UMPSA expands TVET education outreach, strengthens student leadership - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 19 June 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) once again takes a step forward to strengthen the national Technical and Vocational Education and Training (TVET) Agenda by organising the UMPSA Open Day 2025 in conjunction with the National TVET Day Celebration, which took place for two days from 18 to 19 June 2025 at the Sports Complex Hall, UMPSA Gambang Campus.